PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS TANAH ABANG KECAMATAN BATANGHARI LEKO - Ropal Tores (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determine how the influence of service quality on patient satisfaction at Puskesmas Tanah Abang Batanghari Leko District. Field research, where researchers visited Tanah Abang District Health Center Batang Hari Leko by holding question and answer directly to employees who have the authority to provide data and information needed. The result of the research shows that there is influence of service quality to patient satisfaction at Tanah Abang Public Health Center of Batanghari Leko District. The method of analysis used in the research is simple linear regression. This study provides the latest evidence on the effect of service quality on patient satisfaction at Tanah Abang Public Health Center, Batanghari Leko District.